2023
DOI: 10.1111/jdv.19562
|View full text |Cite
|
Sign up to set email alerts
|

Risankizumab for the treatment of genital psoriasis: A 1‐year, real‐world experience

D. Orsini,
P. Frascione,
C. Assorgi
et al.

Abstract: Dear Editor, Genital involvement is frequently reported in patients with psoriasis and is associated with a major impact on quality of life (QoL) and embarrassment in engaging sexual intercourses. [1][2][3] Only 40% of patients reported to have had a previous examination of the genital area, and therefore treatment is often initiated late. 2 Genitals are considered a difficult-to-treat area. 4,5 Topical treatments remain the first-line choice for mild-to-moderate disease. 5 However, corticosteroids are associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
2
0
0
Order By: Relevance
“…12 Among interleukin inhibitors, ixekizumab and risankizumab appear to be the drugs with the highest effectiveness on difficult-to-treat areas, according to data from both clinical trials and real-world experience. [9][10][11][12][13] The safety profile of ixekizumab in our study was very high as no serious AEs or AEs leading to discontinuation were observed, consistent with the results of a 5-year analysis of the UNCOVER-3 study. 14 The main limitations of this study include are the retrospective nature and the absence of a control group, which do not allow the generalization of our findings.…”
Section: Discussionsupporting
confidence: 89%
“…12 Among interleukin inhibitors, ixekizumab and risankizumab appear to be the drugs with the highest effectiveness on difficult-to-treat areas, according to data from both clinical trials and real-world experience. [9][10][11][12][13] The safety profile of ixekizumab in our study was very high as no serious AEs or AEs leading to discontinuation were observed, consistent with the results of a 5-year analysis of the UNCOVER-3 study. 14 The main limitations of this study include are the retrospective nature and the absence of a control group, which do not allow the generalization of our findings.…”
Section: Discussionsupporting
confidence: 89%
“…However, from week 52 onwards, these differences were no longer recorded, except for PASI100 at week 52, which could be explained by a minimal residual PASI in these areas [13,19,22]. In our study, risankizumab was rapidly effective, particularly in patients with genital psoriasis, which improved patient well-being [23]. Our results support the use of risankizumab in patients involving difficultto-treat areas due to its high effectiveness in the long term.…”
Section: Discussionsupporting
confidence: 63%